2013
DOI: 10.1371/journal.pone.0064028
|View full text |Cite
|
Sign up to set email alerts
|

The 53BP1 Homolog in C. elegans Influences DNA Repair and Promotes Apoptosis in Response to Ionizing Radiation

Abstract: 53BP1 contributes to activation of the G2/M checkpoint downstream of ATM and MDC1 in response to ionizing radiation and promotes nonhomologous end-joining (NHEJ) in mammalian cells. In order to determine whether the cellular activities of 53BP1 are conserved in the model organism C. elegans, we analyzed the function of its homolog, HSR-9 in response to DNA damage. Deletion or Mos1-insertion in hsr-9 did not affect the sensitivity of worms to double strand DNA breaks (DSBs), as reflected in embryonic survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
5
11
1
Order By: Relevance
“…Furthermore, we observed that HSR-9, the C. elegans ortholog of the 53BP1 DNA damage response protein, accumulates on Z2/Z3 chromatin with similar dynamics as RAD-51 foci ( Figure 2D). Previous work has shown that HSR-9 accumulates on chromatin specifically during a DNA damage response (Ryu et al, 2013). On the basis of these data, we conclude that Z2/Z3 experience DNA damage as a function of nutrient-dependent cell-cycle reentry.…”
Section: Resultssupporting
confidence: 67%
“…Furthermore, we observed that HSR-9, the C. elegans ortholog of the 53BP1 DNA damage response protein, accumulates on Z2/Z3 chromatin with similar dynamics as RAD-51 foci ( Figure 2D). Previous work has shown that HSR-9 accumulates on chromatin specifically during a DNA damage response (Ryu et al, 2013). On the basis of these data, we conclude that Z2/Z3 experience DNA damage as a function of nutrient-dependent cell-cycle reentry.…”
Section: Resultssupporting
confidence: 67%
“…If the C. elegans BRC-1 / BRD-1 complex biases DSB repair in favor of HR and prevents other DSB repair pathways such as NHEJ, then in smc-5 mutant germ cells, in which HR is impaired, normal BRC-1 / BRD-1 function could end up trapping DSB repair in an unproductive defective pathway. To test the consequences of impaired initiation of NHEJ, we employed a mutant strain for hsr-9 , the C. elegans 53BP1 homolog ( Ryu et al 2013 ). In mammals, 53BP1 antagonizes the function of BRCA1 by promoting initiation of NHEJ while inhibiting HR ( Zimmermann and De Lange 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise in C . elegans , the hypersensitivity of BRCA1 worms to DSBs was rescued by a LIG4 mutation, and that of RAD54 knockdown worms was reversed by 53BP1 or LIG4 mutations [ 26 ]. Similarly, the hypersensitivity of FANCD2 worms and Fanconi anemia patient cells to ICLs was rescued by inhibiting NHEJ [ 13 ].…”
Section: Resultsmentioning
confidence: 99%